Memaknai Nilai-Nilai Kemanusiaan Tokoh Utama Dalam Novel “Hijrah Bang Tato” Karya Fahd Pahdepie - Dina Purnama Sari (Wanastra: Jurnal Bahasa dan Sastra, 2018)
Novel "Hijrah Bang Tatato" by Fahd Pahdepi is a novel based on the true story of the main character, Lalan or Bang Tattoo who experienced the inner struggle to migrate from the dark as a thug to a better and obedient man. As a former thug, Bang Tato as the main character in the novel "Hijrah Bang Tattoo" experienced several phases of life that made him migrate. The phases are experienced by implementing the values of humanity in accordance with the religion it embraces, namely Islam. The meaning of humanity's values of the main character consists of guidance, endeavor, and go home. Therefore, the humanitarian values of the main characters are used as the background of the discussion and the title of this article. The method used is descriptive with the approach of sociology of literature and the meaning of human values itself. The data are examined based on the meaning of the text in the novel by using literature study data collection. Thus, the result is an understanding of the meaning of humanity values of the main characters can be used as a reflection for their readers as a reflection of social reality in society, especially in Indonesia.Key Word : the values of humanity, meaning, the main character, the sociology of literature.